PERBERDAYAAN IBU RUMAH TANGGA MELALUI BAKSO DAN NUGET IKAN BERSAMA LAZISMU PEKANBARU - Irwan Effendi; Mardalisa; Ummi Mardhiah Batubara; Rita Wijaya; Muhammad Arief Wibowo (Journal of Rural and Urban Community Empowerment, 2020)
Poverty is not only caused by the low income of the husbands, but also because family members are not optimally empowered. LAZISMU is a national level zakat institution that is active in community empowerment. One of the targets of its activities is social and economic activities in the form of forming and coaching as well as funding community business groups. This community service program involved housewives and several young women in Kota Pekanbaru. This service is in the form of assistance to the participants so that they have knowledge about processing and varying the methods of processing fish commodities to become fish balls and nuggets. The participants were generally very interested in the training material for making meatballs and fish nuggets. All groups successfully finished making meatballs and fish nuggets with quite savory flavors.